2011
DOI: 10.1109/jqe.2011.2129492
|View full text |Cite
|
Sign up to set email alerts
|

Optical Gain in GaInNAs and GaInNAsSb Quantum Wells

Abstract: Abstract-We have measured the absorption, gain and spontaneous emission spectra of GaInNAsSb (3.3%N), GaInNAs (0.5%N) and GaInAs quantum well structures to compare their merits as laser gain media. The parameters describing the relations between peak gain and current provide only limited insight. From the analysis of absorption spectra we have determined the intrinsic properties of the structures, represented by the product [reduced density of states × matrix element × overlap integral], taking account of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Alternatively, other approaches based on VSL technique with current injection, 25,26 Hakki-Paoli method, 27 and segmented contact technique 28,29 had also been used for characterizing optical gain in electrically injected quantum well lasers. The VSL technique is a very reliable and widely used method for the measurement of the optical gain coefficient in bulk materials, and it allows measuring unambiguously the net modal gain coefficient and the entire gain spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, other approaches based on VSL technique with current injection, 25,26 Hakki-Paoli method, 27 and segmented contact technique 28,29 had also been used for characterizing optical gain in electrically injected quantum well lasers. The VSL technique is a very reliable and widely used method for the measurement of the optical gain coefficient in bulk materials, and it allows measuring unambiguously the net modal gain coefficient and the entire gain spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] An impact of N incorporation is the deterioration of the optical properties as defect induced nonradiative recombination (NRR) increases with increasing N concentration, 15 although recent work has shown that the addition of minimal amount of N ( 0:5%) together with a post-growth annealing treatment (680 C, 10 min) in GaInAsN QW hinder from formation of N-N pairs and clusters and thus do not lead to reduction in the intrinsic gain of the active region. 16 While the NRR could be advantageous for fast saturable aborbers (SAs) and electroabsorption modulators (EAMs) as an additional carrier recombination process, 17,18 it is largely detrimental for the gain properties, with lasing threshold densities remaining relatively high.…”
mentioning
confidence: 99%
“…27 Recent work has reported the superior lasing characteristics of GaInNAs quantum well lasers with very low threshold. [28][29][30] By taking advantage of this progress, the integration of III-V multijunction cells with GaInNAs-containing alloys as one of the cell materials has enabled a record PCE of 43.5%. 31 Other materials including InGaN 32 and InN 33 are currently being pursued, while others such as GaAsBi 34 are being considered for multijunction solar cells.…”
Section: Inorganic Solar Cellsmentioning
confidence: 99%